1994
DOI: 10.1099/0022-1317-75-7-1755
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus particle detected by immunoelectron microscopic study

Abstract: To clarify the morphology of hepatitis C virus (HCV), an indirect immunogold electron microscopic study was carried out on two plasma samples with high HCV RNA titres using polyclonal and monoclonal antibodies specific to the putative HCV envelope protein. Spherical virus-like particles, 55 to 65 nm in diameter with spike-like projections, were found in 1.14 to 1.16 g/ml fractions after sucrose density gradient centrifugation. These particles were found only in HCV-infected blood donors and had morphological f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
124
0
7

Year Published

1995
1995
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(146 citation statements)
references
References 17 publications
15
124
0
7
Order By: Relevance
“…In the culture medium from cells transfected with pTHr, a peak of HCV proteins and RNA coincided in fraction 5, which has the density of 1.16 g͞ml. This density is consistent with the published density of free HCV virions (16). Viral particles were visualized by electron microscopy only in fraction 5 (Fig.…”
Section: Hcv Virion Production and Secretionsupporting
confidence: 80%
“…In the culture medium from cells transfected with pTHr, a peak of HCV proteins and RNA coincided in fraction 5, which has the density of 1.16 g͞ml. This density is consistent with the published density of free HCV virions (16). Viral particles were visualized by electron microscopy only in fraction 5 (Fig.…”
Section: Hcv Virion Production and Secretionsupporting
confidence: 80%
“…HCV is an enveloped virus, as indicated by inactivation after chloroform treatment (Feinstone et al, 1983) and the buoyant density of the virus in sucrose has been determined to be between 1.08 and 1.11 g/ml (Bradley et al, 1991;Hijikata et al, 1993;Kanto et al, 1994;Miyamoto et al, 1992). Recently, electron microscopic examination revealed the spherical morphology of HCV particles with a mean diameter of 55-65 nm (Kaito et al, 1994).…”
mentioning
confidence: 99%
“…Via immunoelectron microscopy using an E2-specific monoclonal antibody, the authors succeeded in demonstrating the presence of specifically labeled spherical particles measuring 50-65 nm in diameter in the culture supernatant from JFH-1 RNA-transfected cells, confirming the early filtration and chimpanzee transmission as well as electron microscopy studies mentioned above. [17][18][19] Furthermore, Wakita et al showed that viral particles had a density of approximately 1.17 g/mL and that infection could be blocked by a monoclonal antibody directed against CD81, confirming the importance of this molecule as a component of the HCV entry pathway. The authors also developed a bicistronic luciferase reporter construct with similar capacity to produce infectious particles as a conveniently measurable read-out.…”
Section: Production Of Recombinant Hcv In Tissue Culturementioning
confidence: 96%
“…17 Subsequent electron microscopy studies confirmed that HCV is an enveloped spherical particle that is 40-70 nm in diameter. 18,19 Thus, it is believed that the HCV envelope contains the viral glycoproteins E1 and E2 and encloses a nucleocapsid composed of multiple copies of core protein, which in turn harbors the viral positive-strand RNA genome.…”
Section: Studying the Viral Particle And Its Entry Pathwaymentioning
confidence: 99%